Altered traits science reveals how meditation changes your mind, brain, and body - Goleman, Daniel 1946-; Davidson, Richard J. (Avery, 2017)
Two New York Times-bestselling authors unveil new research showing what meditation can really do for the brain. In the last twenty years, meditation and mindfulness have gone from being kind of cool to becoming an omnipresent Band-Aid for fixing everything from your weight to your relationship to your achievement level. Unveiling here the kind of cutting-edge research that has made them giants in their fields, Daniel Goleman and Richard Davidson show us the truth about what meditation can really do for us, as well as exactly how to get the most out of it. Sweeping away common misconceptions and neuromythology to open readers' eyes to the ways data has been distorted to sell mind-training methods, the authors demonstrate that beyond the pleasant states mental exercises can produce, the real payoffs are the lasting personality traits that can result. But short daily doses will not get us to the highest level of lasting positive change-even if we continue for years-without specific additions. More than sheer hours, we need smart practice, including crucial ingredients such as targeted feedback from a master teacher and a more spacious, less attached view of the self, all of which are missing in widespread versions of mind training. The authors also reveal the latest data from Davidson's own lab that point to a new methodology for developing a broader array of mind-training methods with larger implications for how we can derive the greatest benefits from the practice. Exciting, compelling, and grounded in new research, this is one of those rare books that has the power to change us at the deepest level. Quelle: Klappentext.